Effects of a vitamin and mineral bolus on beef heifer feedlot performance, feeding behavior, carcass characteristics, and liver mineral concentrations - McCarthy, Kacie L (Transl Anim Sci, 2020)
Crossbred beef heifers (n = 23; initial body weight [BW] = 370 ± 12 kg) housed at the North Dakota State University Beef Cattle Research Complex in Fargo, ND, were used to evaluate the effects of a 250-d slow-release vitamin and mineral bolus on feedlot performance, feeding behavior, carcass characteristics, and liver mineral concentrations. Heifers were assigned to one of two treatments: 1) received no supplemental mineral or vitamin (CON, n = 12) or 2) received two boluses on day 0 (minimum of 3,740 mg Ca, 16,456 mg Mg, 112 mg Na, 11,220 mg Cu, 2,995 mg I, 2,805 mg Mn, 505 mg Se, 48,620 mg Zn, 468 mg Co, 824,296 IU vitamin A, 173,102 IU vitamin D3, and 4,121 IU vitamin E bases on company analysis; Reloader 250 Mineral Bolus, Cargill Inc., Minneapolis, MN; MIN, n = 11). Heifers were fed a total mixed ration containing corn silage, grass hay, dried distillers grains with solubles, and dry-rolled corn (16.05% crude protein, 1.44 Mcal/kg NEg) with no added vitamin or mineral supplement. Feed intake and number and time of visits were recorded for each heifer using the Insentec feeding system (Hokofarm Group B.V., the Netherlands) during the feeding period. Liver biopsies were collected from heifers on days 0, 69, and 134 of the feeding period for analysis of mineral concentrations and analyzed as repeated measures. Heifers were slaughtered after 150 or 169 d on feed, and carcass characteristics were determined. Final BW, average daily gain, dry matter index, gain:feed, and carcass characteristics were not influenced (P > 0.19) by treatment. Control heifers visited feeders more but spent less time per visit and ate less per visit compared with MIN heifers (P < 0.03). No differences (P > 0.06) in liver mineral concentrations were observed between treatments, and concentrations of Se, Cu, Mo, Mn, and Co decreased (P < 0.05) over the feeding period. In this experiment, the slow-release vitamin and mineral bolus evaluated failed to increase liver mineral concentrations during the finishing period or influence heifer performance and carcass characteristics.